Uterine conservation in placenta accrete spectrum (PAS) disorders: A retrospective case series: Is expectant management beneficial in reducing maternal morbidity?. (November 2020) - Lional, Karuna M.; Tagore, S.; Wright, A.M.
Abstract: Objective: To examine whether expectant management confers any benefit on operative morbidity for the management of placenta accrete spectrum (PAS) disorders. Study design: This was a single center retrospective cohort study at a tertiary referral center In Singapore. Women with PAS disorder between January 2006 and December 2017 were identified from the hospital register. Antenatal features, surgical factors and post-operative morbidity were compared between women having caesarean hysterectomy, those having caesarean section with placental removal and women having expectant management, defined as caesarean section with retention of placenta using the student's t and Chi square tests. The natural course, complications and preservation of fertility were examined for women having expectant management. Results: Ninety women with PAS were included. The incidence of PAS was 0.064 %. Mean gestational age (GA) at diagnosis was 26.4 weeks. Elective and emergency deliveries were performed at 36.7 and 32.4 weeks respectively (p = <0.0001). Caesarean hysterectomy, Caesarean section with placenta removal and expectant management (EM) were performed in 51(56.7 %), 16(17.8 %) and 23(25.6 %) women respectively. The mean blood loss (MBL) and surgical time for EM were significantly lower than those for caesarean hysterectomy 0.52 L vs 3.17 L (p < 0.0001) and 70.8 min vs 171.6 min (p < 0.0001). The advantage of lower blood loss with expectant management persisted even after blood loss at delayed hysterectomy was considered (1284.09 mL vs 3168.72 mL (p-value <0.0001)). Uterine preservation with EM was successful in 61 % (14/23) women. Although nine women (39 %) in this group needed hysterectomy most complications were minor and presented within three months. The mean follow up overall was 13 months. Conclusion: Traditionally caesarean hysterectomy has been the main surgical approach for PAS. Our study consolidates existing evidence for expectant management being an option for a select group of patients to avoid complications associated with hysterectomy and allow uterine preservation.